Effectiveness of Science Learning Using Physics Kit Media on Conceptual Understanding - Susanti, Susanti; Ernawati, Tias; Septiani, Devi (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2023)
This study aims to determine the effectiveness of using Physics Kit media in improving conceptual understanding in physics. The research was conducted during the 2023/2024 academic year. This study is a quasi-experimental research. Data were collected using test instruments. The subjects of the study were 21 students from the Science Education program. The data analysis technique used was N-Gain. The results indicate that learning using Physics Kit media is effective in enhancing students' conceptual understanding in physics. The N-Gain percentage of 86.33% falls into the high category, with an effective interpretation.